Idea Wspólnego Europejskiego Domu a egoizmy narodowe i regionalne: przykład Hiszpanii - Jaroszyk, Joanna (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2008)
The term ‘Common European Home’was coined in 1987 by Mikhail Gorbachev to describe the future policy of the Soviet Union towards Eastern Europe. At present this notion has lost its disquieting tone, which was related to the statement made by the Soviet Political Bureau: ‘a stifling embrace, a suffocating hug’. Nowadays, this idea covers various models of European integration, and is expressed in both the hopes and concerns of the states that participate in this process. The economic and political integration of European states has been a continuous and dynamic process. The question of its further direction has become particularly important after the French said ‘non’ to the European Constitution. This has refueled disputes over existing integration models, which are focused around the opposing concepts of a Federal Europe and a Europe of Homelands as a confederation. It is of significant importance since the process of Europeization has been parallel to the process of regionalization inside the national European states. Regionalization mainly followed from the demands of autonomists, but sometimes was initiated by central governments as part of the process of decentralization. At present, European regions have increased their economic significance and have won more rights and authority inside their states. Consequently, they have aspired to become independent forces for globalization and Europeization. This process can be exemplified by Spain. After forty years of Franco’s dictatorship, where any form of regional autonomy whatsoever was rejected, in 1975 a slow democratization process began.